San Martín del Rey Aurelio : conocer el municipio / Juan José Fernández Laviana, Graciano Torre González, Severino Antuą González - Torre González, GracianoAntuą, Severino; Fernández Laviana, Juan José
Portada y texto contrapuestos, en Español y asturiano | Bibliografía